KONSEP PENDIDIKAN PEREMPUAN DARI PERSPEKTIF KH. HASYIM ASY'ARI - Zidal Haq, M. Ilham; Hosna, Rofiatul (STAI Pelabuhan Ratu, 2024)
KH. Hasyim Asy'ari appears as a figure who fights for women's emancipation. KH. Hasyim Asy'ari has made many real contributions to the world of education. However, there has been no in-depth study of his thoughts on the concept of women's education. He made various efforts and methods to realize education for women. Among them are offering ideas about the concept of women's education. This research wants to know about KH's concept of women's education. Hasyim Asy'ari and its relevance to the current national education system. This research approach is qualitative with a library research type of research (literature review). The data analysis uses content analysis and descriptive analysis methods, and concludes according to the research focus. KH. Hasyim Asy'ari offers an education concept that places women equal to men in the right to receive education, without discrimination, and is oriented towards character building and devotion to God so that they are able to understand their obligations, responsibilities and rights as women.